A Scoping Review of an HIV/AIDS-Related Stigma-Reduction Intervention for Professionals and Students from Health-Related Disciplines. Issue 2 (2nd April 2020) - Ma, Haixia; Loke, Alice Yuen
Abstract: Objective : To review HIV/AIDS-related stigma-reduction interventions for professionals and students from health-related disciplines. Methods : A scoping review was conducted to identify the key characteristics of the interventions in electronic databases up to April 2018. Results : 45 studies were included in the review. The majority of interventions adopted a combination of approaches. Interventions with multiple approaches and a longer duration/multiple sessions are more likely to achieve the intended results. While standardized measurements of stigmatizing attitudes toward people living with HIV/AIDS (PLWHA) were lacking. Conclusion : Most of the included studies showed promise results. However, standardized measurements should be developed.